Heteroepitaxy of Ge on singular and vicinal Si surfaces: elastic field symmetry and nanostructure growth. (28th May 2015) - Persichetti, L; Sgarlata, A; Fanfoni, M; Balzarotti, A
Abstract: Starting with the basic definition, a short description of a few relevant physical quantities playing a role in the growth process of heteroepitaxial strained systems, is provided. As such, the paper is not meant to be a comprehensive survey but to present a connection between the Stranski–Krastanov mechanism of nanostructure formation and the basic principles of nucleation and growth. The elastic field is described in the context of continuum elasticity theory, using either analytical models or numerical simulations. The results are compared with selected experimental results obtained on GeSi nanostructures. In particular, by tuning the value of quantities such as vicinality, substrate orientation and symmetry of the diffusion field, we elucidate how anisotropic elastic interactions determine shape, size, lateral distribution and composition of quantum dots.